Avaliação da usabilidade de videoclipe para aprendizagem da fisiologia da lactação por profissionais do serviço de atenção primária à saúde - Machado, Liane Bahú (2023)
Introduction: The professional in the Primary Health Care services needs to provide guidelines based on scientific evidence to the nursing mother and her family to promote learning and enable decision-making and safe practices for the establishment and maintenance of maternal nutrition. These guidelines contemplate lactation physiology, which is a complex and abstract content for which the use of Educational Technologies is one of the viable options to promote learning through health education among users. Objectives: Evaluate the usability of an Educational Technology of the videoclip type for the learning of lactation physiology by professionals of the Primary Health Care service; and identify the barriers and facilitators for the use of this technology as a support tool for the actions carried out by these professionals in the local context. Method: Cross-sectional study guided by the Model of Translation of Knowledge in Action. Carried out in the municipality of Santa Maria, in Rio Grande do Sul, with 71 healthcare professionals who assist children in Primary Care. After the approval of the Research Ethics Committee, a self-application electronic form was used as the System Usability Scale instrument and open questions about barriers and facilitators for the use of the video clip. The average was 68 points. To evaluate the correlation between quantitative variables, the Spearman correlation test was used. A significance level of 5% was considered for the established comparisons. The Cronbach's Alpha was 0.90, which indicates the reliability of the instrument in this population. Results: The professionals evaluated the usability of the video clip as excellent (total score 85), wich obtained a positive association with the professional having a refresher course in child health (p=0.023). The participants have the expectation that the use of this video clip will be a support tool for the actions that they develop in the service (91.5%), are motivated to use it (85.9%), believe they have knowledge of the topic to use it (98.6%) and believe they are able to use it (95.8%). They would indicate the video clip so that other professionals could use it in permanent education and with pregnant women, puerperal women and in their support network as a health education tool. Also, recognized that they could use it in training, indicating it to health area academics. They identify situations in the work environment that could be barriers to use, such as the restricted time of attendance, the unavailability of resources to present the videoclip to the users, resistance to the use of technological media by professionals and the level of education of users. Conclusion: The satisfaction degree of the health professionals with the video clip for learning lactation physiology points to the potencial usability of this tool for the introduction of the subject of maternal nutrition for permanent education through the professionals themselves and/or mediated by them for use with users in primary health care services. There is a need to minimize barriers of physical infrastructure and human resources for the application of educational technology in the local context.